Working in virtual environments: Three practical collaborative web tools - Staiger Rivas, Simone; Shelton, P.; Kosina, Petr; White, N. (2009)
In our work as researchers and development workers, we are tasked with producing more and more information, even though we complain about information overload. Collaboration is increasingly complex but is fundamental to achieving our goal of reducing poverty and hunger through high-quality international agricultural research, partnership and leadership. Recent developments in information and communications technology (ICT) can make data, information and knowledge more available, accessible and applicable (CGIAR ICT-KM Program, 2008), which should contribute significantly to the effectiveness of our collaborative work. This Brief describes three web tools that can enhance participation and collaboration in geographically distributed teams: wikis, blogs, and social bookmarking. Each tool is briefly explained, examples of use are provided and analyzed, and some useful practices are suggested. It is our assumption that by making it easy to produce and share information, we can empower our staff, engage more effectively with our partners, and reach a wider audience of end users.